Development and Correlation of Work-Related Behavior and Experience Patterns, Burnout and Quality of Life in Medical Students from their Freshmanship to the First State Examination - Scholz, Michael; Neumann, Carolin; Steinmann, Cornelia; Hammer, Christian; Schröder, Antje; Essel, Nicole; Paulsen, Friedrich; Burger, Pascal H. M. (Psychotherapie Psychosomatik Medizinische Psychologie, 2015)
Symptoms of burnout are common among medical students. Although they usually start with a good health status, their condition deteriorates over the course of their studies. In our study ESTRELLAS we examined 530 medical students in the preclinical semesters with validated psychological questionnaires. The longer the students were studying, the more showed risky working habits. Cognitive and emotional burnout symptoms increased coincidentally in their intensity, whereas the mental quality of life continuously deteriorated. Medical students' cognitive and emotional burnout symptoms are constantly increasing from the beginning of their studies. Contemporaneously, the mental quality of life is deteriorating. This might be based on a drastic change towards risky working habits. We suggest to actively work against this process to keep our motivated students and prospective physi-cians productive and in good mental health.
EVALuna2:4431

Differentiation Patterns of Immortalized Human Meibomian Gland Epithelial Cells in Three-Dimensional Culture - Asano, Nagayoshi; Hampel, Ulrike; Garreis, Fabian; Schröder, Antje; Schicht, Martin; Hammer, Christian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2018)
Purpose: To establish a simplified three-dimensional (3D) meibomian gland culture model using a meibomian gland epithelial cell (HMGEC) line that might be a useful tool to gain deeper insights into meibomian gland dysfunction. For this purpose, 3D differentiation patterns and growth characteristics of HMGECs were studied on various membranes/scaffolds as well as in hanging drops. Methods: Several types of inserts consisting of different materials (Millicell-HA, Millicell-PCF, ThinCert, and Alvetex) as well as hanging drop culture were analyzed. Culture conditions were optimized employing exposure to air (air-lift) and different cell culture media for a maximum of 28 days. To characterize cell differentiation in the developed 3D model, the expression pattern of cytokeratins was investigated by immunohistochemistry. Sudan III staining was performed for detection of lipid formation and transmission electron microscopy (TEM) was used for ultrastructural analysis. Results: Only Alvetex scaffolds and the hanging drop method revealed satisfactory results with regard to 3D culture. Continuous use of proliferation medium (serum-free keratinocyte medium containing epidermal growth factor and bovine pituitary extract) and air-lift were important steps for HMGEC differentiation in 3D culture. However, HMGECs only reached a differentiating state and never became mature or hypermature. When cultured in hanging drops, HMGECs showed serum-induced keratinization processes. Conclusions: HMGECs have the capability to differentiate in a long-term 3D culture, especially when adapted to an air-rich environment. However, even in the 3D format, HMGECs only reach a state of differentiating meibocytes.
EVALuna2:35318

In vitro effects of sex hormones in human meibomian gland epithelial cells - Schröder, Antje; Abrar, Daniel; Hampel, Ulrike; Schicht, Martin; Paulsen, Friedrich; Garreis, Fabian (Experimental Eye Research, 2016)
Meibomian gland dysfunction (MGD) is considered the most common cause of dry eye disease (DED). Sex hormones seem to play a role in the pathogenesis of MGD although their involvement is not completely understood. Therefore, in the present study we evaluated the effect of dihydrotestosteron (DHT) and estradiol (β-Est) on an immortalized human meibomian gland epithelial cell line (HMGEC). Protein expression of sex hormone receptors in HMGEC was investigated by western blot. Ultrastructural morphology, Sudan III lipid staining, cell proliferation as well as vitality assays were performed. Furthermore, expression of MGD-associated markers for keratinization (hornerin, involucrin and CK6), proliferation (CK5 and CK14) and lipid synthesis (fatty acid synthase and stearoyl-CoA desaturase) were analyzed by real time RT-PCR. Western blot revealed presence of androgen receptor (AR), estrogen receptors α and -β (ERα, ERβ) and progesterone receptor (PR) in HMGEC. PR, ERα and ERβ expression was significantly induced under cultivation with serum, whereas sex hormones stimulation showed no further effect on protein expression of PR, ERα and ERβ. Our results showed no impact of MGD-associated sex hormones to cellular morphology and lipid accumulation in HMGEC. Cell proliferation was slightly induced through application of sex hormones and supplementation of calcium. However, both sex hormones and calcium altered gene expression of MGD-associated markers. Especially keratinization genes hornerin (HRNR) and cornulin (COR) were induced after application of sex hormones and calcium in serum-free cultivated HMGEC. This may promote keratinization processes that are associated with MGD. Further investigations are necessary to analyze the (hyper)keratinization processes that occur during MGD and using HMGEC as an in vitro model.
EVALuna2:35345

Serum-induced keratinization processes in an immortalized human meibomian gland epithelial cell line - Hampel, Ulrike; Schröder, Antje; Mitchell, Todd; Brown, Simon; Snikeris, Peta; Garreis, Fabian; Kunnen, Carolina; Willcox, Mark; Paulsen, Friedrich (PLoS ONE, 2015)
The aim of this study was to evaluate a human meibomian gland epithelial cell line (HMGEC) as a model for meibomian gland (patho)physiology in vitro.HMGEC were cultured in the absence or presence of serum. Sudan III lipid staining, ultrastructural analysis and lipidomic analyses were performed. Impedance sensing, desmoplakin 1/2 mRNA and cytokeratin (CK) 1, 5, 6, 14 levels were evaluated. Serum containing medium supplemented with higher serum, glucose, an omega-3 lipid cocktail, eicosapentaenoic acid or sebomed medium were investigated for lipid accumulation and ultrastructural morphology.Lipid droplet accumulation in HMGEC was induced by serum containing media after 1 day, but decreased over time. Cultivation in serum induced desmosome and cytokeratin filament formation. Desmoplakin 1/2 gene levels were significantly upregulated after 1d of serum treatment. Furthermore, the normalized impedance increased significantly. Lipidome analysis revealed high levels of phospholipids (over 50%), but very low levels of wax ester and cholesteryl esters (under 1%). Stimulation with eicosapentaenoic acid increased lipid accumulation after one day.Serum treatment of HMGEC caused lipid droplet formation to some extent but also induced keratinization. The cells did not produce typical meibum lipids under these growth conditions. HMGEC are well suited to study (hyper)keratinization processes of meibomian gland epithelial cells in vitro.
EVALuna2:4445

Upregulation of Transient Receptor Potential Vanilloid Type-1 Channel Activity and Ca2+ Influx Dysfunction in Human Pterygial Cells - Garreis, Fabian; Schröder, Antje; Reinach, Peter S.; Zoll, Stefanie; Khajavi, Noushafarin; Dhandapani, Priyavathi; Lucius, Alexander; Pleyer, Uwe; Paulsen, Friedrich; Mergler, Stefan (Investigative Ophthalmology & Visual Science, 2016)
PURPOSE: The heat-sensitive transient receptor potential vanilloid type-1 (TRPV1) channel (i.e., capsaicin [CAP] receptor) is upregulated in numerous cancers. This study determined if this response occurs in fresh and cultured hyperplastic human pterygial epithelial tissues. METHODS: Reverse transcriptase PCR and quantitative real-time PCR, along with immunohistochemistry and Western blotting, characterized TRPV1 expression patterns in pterygial and healthy conjunctival tissue, primary and immortalized pterygial cells (hPtEC), and primary and immortalized conjunctival epithelial cells (HCjEC). Imaging of Ca2+ and planar whole-cell patch-clamping evaluated TRP channel activity. An MTS assay measured cell metabolic activity and a cell growth assay monitored proliferation. RESULTS: Capsaicin (20 μM) and elevating bath temperature above 43°C activated Ca2+ transients more in hPtEC than HCjEC. Capsaicin induced corresponding changes in inward currents that were inhibited by 20 μM capsazepine (CPZ). Vascular endothelial growth factor (VEGF) also increased Ca2+-influx and induced corresponding inward currents more in hPtEC than in HCjEC, whereas CPZ (20 μM), BCTC (20 μM), or La3+ (500 μM) reduced these responses, respectively. Whereas epidermal growth factor (EGF) increased proliferation more in hPtEC than in HCjEC, VEGF had no effect on this response. Capsazepine suppressed hPtEC proliferation induced by EGF and VEGF, whereas it was cytotoxic to HCjEC. CONCLUSIONS: Mitogenic responses to EGF and VEGF are mediated through TRPV1 transactivation. Only in hPtEC do the increases in proliferation induced by EGF exceed those in HCjEC. Therefore, TRPV1 is a potential drug target whose clinical relevance in treating pterygium warrants further assessment.
EVALuna2:35348